The great crash 1929 - Galbraith, John K. (Boston Houghton Mifflin Company, 1997)
The Atlantic Monthly said, "Economic writings are seldom notable for their entertainment value, but this book is. Galbaiyhs prose has grace and wit, and he distills a good deal of sardonic fun from the whoping errors of the nations oracles and the wondrous antics of the financial community".
Keywords: Fiction